Sodobno načrtovanje cestne infrastrukture - Gruev, Marta (Urbani izziv, 2003)
Transport infrastructure signifies the framework of the spatial structure, defining its extents and limitations. Because transport development simultaneously dimensions extents of economic and urban development and growththe completion of the highway cross was envisaged as the priority project of the young country's development and defined with the National programme for highway construction in Slovenia. The article presents a quick overview of contemporary planning of transport (road) infrastructure, which includes areas from the supra-national level of highways to the capillary roadnetwork. It limits itself to content, as well as pertaining and factual review of legislative processes, which are the basis for planning and maintenance of road infrastructure, without evaluation of efficiency of laws or measures.
Keywords: ceste; pravna ureditev; prometna infrastruktura; prostorski razvoj; prostorsko planiranje; razvojna strategija; Slovenia; Slovenija; spatial planning; statute; zakoni